Expression of a Neuroendocrine Gene Signature in Gastric Tumor Cells from CEA 424-SV40 Large T Antigen-Transgenic Mice Depends on SV40 Large T Antigen - Ihler, Fritz; Vetter, Elena Viviana; Pan, Jie; Kammerer, Robert; Debey-Pascher, Svenja; Schultze, Joachim L.; Zimmermann, Wolfgang; Enders, Georg (PLOS ONE, 2012)
Background A large fraction of murine tumors induced by transgenic expression of SV40 large T antigen (SV40 TAg) exhibits a neuroendocrine phenotype. It is unclear whether SV40 TAg induces the neuroendocrine phenotype by preferential transformation of progenitor cells committed to the neuroendocrine lineage or by transcriptional activation of neuroendocrine genes. Methodology/Principal Findings To address this question we analyzed CEA424-SV40 TAg-transgenic mice that develop spontaneous tumors in the antral stomach region. Immunohistology revealed expression of the neuroendocrine marker chromogranin A in tumor cells. By ELISA an 18-fold higher level of serotonin could be detected in the blood of tumor-bearing mice in comparison to nontransgenic littermates. Transcriptome analyses of antral tumors combined with gene set enrichment analysis showed significant enrichment of genes considered relevant for human neuroendocrine tumor biology. This neuroendocrine gene signature was also expressed in 424GC, a cell line derived from a CEA424-SV40 TAg tumor, indicating that the tumor cells exhibit a similar neuroendocrine phenotype also in vitro. Treatment of 424GC cells with SV40 TAg-specific siRNA downregulated expression of the neuroendocrine gene signature. Conclusions/Significance SV40 TAg thus appears to directly induce a neuroendocrine gene signature in gastric carcinomas of CEA424-SV40 TAg-transgenic mice. This might explain the high incidence of neuroendocrine tumors in other murine SV40 TAg tumor models. Since the oncogenic effect of SV40 TAg is caused by inactivation of the tumor suppressor proteins p53 and RB1 and loss of function of these proteins is commonly observed in human neuroendocrine tumors, a similar mechanism might cause neuroendocrine phenotypes in human tumors.